Gender trouble : feminism and the subversion of identity - Butler, Judith, 1956- (Routledge, 1999)
"Thrilling and provocative, this book is perhaps the essential work of contemporary feminist thought. Its intellectual reference points include Foucault and Freud, Wittig, Kristeva and Irigaray. Indeed, few other academic works have roused passions as much. One of the most talked-about scholarly works of the past fifty years, Judith Butler's Gender Trouble is as celebrated as it is controversial. Butler argues that traditional feminism is wrong to look to a natural, 'essential' notion of the female, or indeed of sex or gender. She starts by questioning the category 'woman': who does it include, and who decides who it includes? And she continues in this vein; 'the masculine' and 'the feminine' are not biologically fixed but culturally presupposed. Best known however, yet also most often misinterpreted, is Butler's concept of gender as a reiterated social performance rather than the expression of a prior reality." --